2010
DOI: 10.1007/s11010-010-0614-3
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry and biochemical analysis of RNA polymerase II: targeting by protein phosphatase-1

Abstract: Transcription of eukaryotic genes is regulated by phosphorylation of serine residues of heptapeptide repeats of the carboxyterminal domain (CTD) of RNA polymerase II (RNAPII). We previously reported that protein phosphatase-1 (PP1) dephosphorylates RNAPII CTD in vitro and inhibition of nuclear PP1-blocked viral transcription. In this article, we analyzed the targeting of RNAPII by PP1 using biochemical and mass spectrometry analysis of RNAPII-associated regulatory subunits of PP1. Immunoblotting showed that PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Although the position of β14 varies depending on the PP1 regulatory protein bound, this is the first time, to our knowledge, that PP1 loop 21 …”
Section: Gsrpgmentioning
confidence: 82%
See 2 more Smart Citations
“…Although the position of β14 varies depending on the PP1 regulatory protein bound, this is the first time, to our knowledge, that PP1 loop 21 …”
Section: Gsrpgmentioning
confidence: 82%
“…S11A). PNUTS binding results in a ∼3.5-Å shift of the PP1 C-terminal strand away from helix αB and the C-terminal groove and a second ∼3.5-Å shift of PP1 loop 21 …”
Section: Pnuts Residue Leu407mentioning
confidence: 99%
See 1 more Smart Citation
“…RNA polymerase II could be a third PP1 substrate; we have previously shown that the C-terminal domain of RNA polymerase II is indeed dephosphorylated by PP1 (39). Our recent study showed that NIPP1 can serve as an RNA polymerase II-targeting subunit of PP1 (40), and thus altered RNA polymerase II dephosphorylation could also be considered as a potential inhibitory mechanism. Interestingly, the results presented here indicate that despite the expression of cdNIPP1, cells remained viable even though the association of CDK9 with 7SK RNA was increased.…”
Section: Discussionmentioning
confidence: 98%
“…As shown in Fig. 1A, Xenopus Pnuts is well conserved to the human homolog, containing the same set of functional domains, including the middle RVX(F/W)P motif that binds PP1 phosphatase (20,21,27), the YLP motif that associates with TRF2 and modulates telomere stability (25), the N-terminal RNA-binding motif that is potentially related to its function in transcriptional control (21,35,36), and the C-terminal zinc finger motif that has not been functionally characterized. To examine the role of Pnuts in M-phase exit, recombinant Pnuts proteins with GST or MBP tag were purified and added to Xenopus extracts at severalfold over endogenous Pnuts level (Figs.…”
Section: Pnuts Overexpression Suppresses Both Meiotic and Mitoticmentioning
confidence: 99%